If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 27k + 20k = -3k(9k + -3) Combine like terms: 27k + 20k = 47k 47k = -3k(9k + -3) Reorder the terms: 47k = -3k(-3 + 9k) 47k = (-3 * -3k + 9k * -3k) 47k = (9k + -27k2) Solving 47k = 9k + -27k2 Solving for variable 'k'. Combine like terms: 47k + -9k = 38k 38k + 27k2 = 9k + -27k2 + -9k + 27k2 Reorder the terms: 38k + 27k2 = 9k + -9k + -27k2 + 27k2 Combine like terms: 9k + -9k = 0 38k + 27k2 = 0 + -27k2 + 27k2 38k + 27k2 = -27k2 + 27k2 Combine like terms: -27k2 + 27k2 = 0 38k + 27k2 = 0 Factor out the Greatest Common Factor (GCF), 'k'. k(38 + 27k) = 0Subproblem 1
Set the factor 'k' equal to zero and attempt to solve: Simplifying k = 0 Solving k = 0 Move all terms containing k to the left, all other terms to the right. Simplifying k = 0Subproblem 2
Set the factor '(38 + 27k)' equal to zero and attempt to solve: Simplifying 38 + 27k = 0 Solving 38 + 27k = 0 Move all terms containing k to the left, all other terms to the right. Add '-38' to each side of the equation. 38 + -38 + 27k = 0 + -38 Combine like terms: 38 + -38 = 0 0 + 27k = 0 + -38 27k = 0 + -38 Combine like terms: 0 + -38 = -38 27k = -38 Divide each side by '27'. k = -1.407407407 Simplifying k = -1.407407407Solution
k = {0, -1.407407407}
| 13(x+1)-4x=85 | | xsqared+3xsquared=10squared | | 24x+4(6-x)=2(x+19)+4x | | 2(w-8)+3w= | | 16x^2+3x-4=0 | | 6-2(4-4x)=0 | | 35x^2+49x=168 | | 5(w-4)-(1-8w)=12w | | 35x^2+49=168x | | 48-2x=5x+7 | | -(-2+n)=-4+11n | | 35x^2+49=168 | | 4y^2-4y-24=0 | | 3-2(8x+4)=5 | | 6-(2x-6)=7-3x | | -4x+(4+6x)=10 | | 5x+2=25+50x | | 4t^2-13t-35=0 | | 3x^3-2x^2-3x-4= | | x^2+7x+3=3 | | 374+78x+4x^2=644 | | 287.64=9(0.05m+21.70+0.30(21.70)) | | -6-(4-b)=30 | | 3y+9x+5y= | | 9y-8=8y | | 0=-16t^2+75t-23 | | .4+7=7 | | -x+7=5x+11 | | 12t+4=16t-8 | | -7x+3-5x=3x-31+2x | | 7x+21=-21-3x | | 6-1.5x=24 |